The human ventilatory response to step changes in end-tidal PO2 of differing amplitude. - Paterson, D; Clement, I; Howard, L; Nagyova, B; Robbins, P (1993)
This study assessed whether the form of the peripheral chemoreflex response to hypoxia depends on the magnitude of the stimulus. Two amplitudes of square-wave hypoxic stimulation were employed: small amplitude (SO) PETO2 from 63.2 to 54.9 Torr, and large amplitude (LO) PETO2 from 73.0 to 48.0 Torr. Each was studied at two levels of PETCO2: 2 Torr above resting PETCO2 (EC), and 7 Torr above resting PETCO2 (HC). Each protocol was repeated 6 times on 5 subjects. To assess the form of the response, a simple first-order model was fitted to the data which incorporated a pure delay (Td) and time constant (tau). Average parameter values (sec) were: ECSO tau = 4.07, Td = 6.69; ECLO tau = 8.82, Td = 4.91; HCSO tau = 5.22, Td = 7.08; HCLO tau = 9.96, Td = 4.39. ANOVA demonstrated modest but significant differences for loge(tau) (P < 0.01) and Td (P < 0.02) between the two hypoxic step magnitudes, with tau longer and Td shorter for the larger step size, but no differences were found between the parameter values for the two CO2 levels. We conclude that the form of the response of the peripheral chemoreflex to hypoxia depends upon the magnitude of the stimulus.